Carbonea tephromelae M. Svensson & M. Westb. 2021, sp. nov. - Svensson, Måns; Westberg, Martin (Zenodo, 2021)
Carbonea tephromelae M.Svensson & M.Westb. sp . nov . Fig. 2A–2E MycoBank No: MB840305 Holotype:— SWEDEN. Lule lappmark: Jokkmokk par., Padjelanta National Park, 11 km WNW of Staloluokta, S slope of Unna Duvgge (Unna Toki), c. 460 m NE of small cabin, 67.34787˚N, 16.45453˚E, elev. 703 m, S-exposed slope in bare mountain region, on Tephromela atra on rock, 5 August 2020, Martin Westberg PAD384 (UPS L-994014). Diagnosis :—Distinguished from other Carbonea species with a colourless hypothecium by having globose to broadly ellipsoid spores and by growing on Tephromela atra . Etymology :—Named after its host species Tephromela atra (Huds.) Hafellner. Description :—Lichenicolous fungus. Thallus inapparent, inhabiting the thallus of Tephromela atra , which darkens and is apparently damaged due to the infection (Fig 2A). Apothecia black, shining, c. 0.2–0.4(–0.5) mm diam., rounded to flexuose, sessile on the thallus of the host. Disc flat or becoming somewhat convex in larger apothecia. Proper exciple concolorous with the disc, persistent, narrow, raised or level with the disc in older apothecia. Apothecial anatomy: Proper exciple opaque, appearing black even in thin sections, densely pigmented blue-green (Cinereorufa-green sensu Meyer & Printzen 2000) in the upper part, in the lower part beneath the hypothecium in mixture with a dark brown pigment, c. 20–45(–85) µm thick, composed of radiating, thick-walled hyphae with c. 2 µm wide lumina. Hymenium colourless or faintly blue-green, c. 50–75 µm tall. Epihymenium strongly blue-green (Cinereorufa-green), N+ red, K−. Hypothecium colourless, without visible crystals in polarized light. Paraphyses simple or forked near the tips, septate and often slightly constricted at the septa, c. 1.5 µm in midhymenium, tips colourless, cylindrical to clavate, 1.5–2.5 µm wide. Asci of Lecanora - type, 8-spored, clavate, 41–49 × 12–19 µm. Ascospores broadly ellipsoid to globose, (7.5–)8.66 ±0.97(–11) × (5.5–)6.81 ±0.71(–8.5) µm; l/b ratio (1–)1.28 ±0.2(– 1.67) (n=57). Distribution and habitat :—The species is so far known from two localities in northern Sweden. Its host Tephromela atra , however, is a common and widespread lichen on both calcareous and non-calcareous rocks. We searched for Carbonea tephromelae in 264 collections of T . atra sensu lato in herb. UPS, of which 183 were from Europe, 29 from North America, 22 from Oceania, 14 from Asia, 12 from South America and 4 from Africa, without finding any additional specimens. Most of the examined collections were from lowland localities, and it is possible that C . tephromelae is restricted to or at least more common in alpine to subalpine localities. Additional specimens examined: — SWEDEN. Lule lappmark: Jokkmokk par., Padjelanta National Park, 11 km WNW of Staloluokta, S slope of Unna Duvgge (Unna Toki), 67.35390˚N, 16.45239˚E, elev. 818 m, steep S-exposed slope in bare mountain region with partly calcareous rocks, on Tephromela atra on rock, 2 August 2020, M . Westberg PAD133 (UPS L-994013). Lycksele lappmark: Tärna par., Ume älv, Över-Umans sydvästligaste vik, ”Kobresia-ön” [= the river Ume älv, the southwesternmost inlet of Lake Över-Uman, ”the Kobresia-island”], 66˚06–07’N, 14˚32–33’E, alt. 530 m, kalkfri glimmerskiffer på holmens toppdel [= Calcium-free mica schist on the highest part of the islet], 19 August 1960, G . E . Du Rietz 951d (UPS L-115703); Ume älv, Över-Umans sydvästligaste vik, ”ön 138” [= the river Ume älv, the southwesternmost inlet of Lake Över-Uman, ”the island 138”], 66˚06–07’N, 14˚32–33’E. Alt. 530 m. Lösa stenar i andra Dryas -backen ovan stranden [= loose rocks in the second Dryas -slope above the shore], 29 August 1960, G . E . Du Rietz 2197i (UPS L-119284). : Published as part of Svensson, Måns & Westberg, Martin, 2021, A new lichenicolous species of Carbonea (Ascomycota, Lecanoraceae) from northern Sweden, pp. 221-230 in Phytotaxa 522 (3) on pages 225-226, DOI: 10.11646/phytotaxa.522.3.5, http://zenodo.org/record/5560427 : {"references": ["Meyer, B. & Printzen, C. (2000) Proposal for a standardized nomenclature and characterization of insoluble lichen pigments. Lichenologist 32: 571 - 583. https: // doi. org / 10.1006 / lich. 2000.0294"]}